2016
DOI: 10.1371/journal.pone.0155268
|View full text |Cite
|
Sign up to set email alerts
|

Normative Values for Intertrial Variability of Motor Responses to Nerve Root and Transcranial Stimulation: A Condition for Follow-Up Studies in Individual Subjects

Abstract: ObjectiveIntertrial variability (ITV) of motor responses to peripheral (CMAP) and transcranial (MEP) stimulation prevents their use in follow-up studies. Our purpose was to develop strategies to reduce and measure CMAP and MEP ITV to guide long-term monitoring of conduction slowing and conduction failure of peripheral and central motor pathway in the individual patient.MethodsMaximal compound muscle action potentials to High Voltage Electrical Stimulation (HVES) of lumbo-sacral nerve roots (r-CMAP) and activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…This study assessed the reliability of TMS-related measures collected from the TA muscle at rest and at 5%MVC of a population of 24 healthy older adults (mean age of 62 years). These measures, although acquired with the rapid protocol for SR curves proposed in [ 9 ], were similar, in terms of magnitude, to those previously obtained on the TA muscle of healthy subjects [ 6 , 18 , 29 , 30 , 47 ]. Comparisons were not possible for the AURC and I50, since no previous studies evaluated this outcome on the TA muscle.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This study assessed the reliability of TMS-related measures collected from the TA muscle at rest and at 5%MVC of a population of 24 healthy older adults (mean age of 62 years). These measures, although acquired with the rapid protocol for SR curves proposed in [ 9 ], were similar, in terms of magnitude, to those previously obtained on the TA muscle of healthy subjects [ 6 , 18 , 29 , 30 , 47 ]. Comparisons were not possible for the AURC and I50, since no previous studies evaluated this outcome on the TA muscle.…”
Section: Discussionsupporting
confidence: 65%
“…Compared to absolute reliability, relative reliability was more commonly investigated in the literature. Several studies have estimated ICC values for TMS outcomes in TA muscle on healthy subjects [ 6 , 18 , 29 , 30 , 47 ]. Good relative reliability (ICC>0.70) was generally found for resting MT, slope, latency, silent period, and MEP amplitude; only one study [ 30 ] observed a moderate reliability for latency (ICC of 0.55–0.71 during isometric muscle contractions of 10% to 60%MVC) and silent period (ICC of 0.16–0.40).…”
Section: Discussionmentioning
confidence: 99%
“…That is, time lag between flavor detection in the brain and time of signaling by the hand might have affected the determination of the respiratory phase wherein detection signals occurred. A recent study reports that transcranial magnetic stimulation of the motor area can evoke potentials in the flexor hallucis brevis and that the average latency period for evoked potentials is less than 40 msec [13]. In this study, the average latency was 1.2% of the average time of the average respiratory cycle, including the pausing phase (Figure 2(b)).…”
Section: Discussionsupporting
confidence: 56%
“…Latencies and peak-to-peak amplitudes were quantified and replicates averaged. All recording electrode localizations were measured from landmarks, detail marked in ink, and photographed for accurate replication in subsequent sessions ( 73 ).…”
Section: Methodsmentioning
confidence: 99%